(untitled) (The Research of Medical Science Review, 2025)
Cardiovascular diseases (CVDs) remain a primary source of global morbidity and mortality, necessitating continuous innovations in surgical procedures to improve patient outcomes. Myocardial preservation during cardiac surgery, particularly with cardiopulmonary bypass (CPB), plays a critical role in avoiding intraoperative and postoperative complications. This study investigates the comparative effectiveness of Del Nido cardioplegia versus conventional cardioplegia on postoperative outcomes in patients undergoing coronary artery bypass grafting (CABG) and valvular heart operations. The study utilized a retrospective comparative approach and was conducted at the Choudhary Pervaiz Elahi Institute of Cardiology, Wazirabad, a tertiary cardiac care facility. A total of 100 adult patients who underwent cardiac surgery between January 2023 and December 2023 were included and divided into two equal groups: 50 patients receiving Del Nido cardioplegia and 50 receiving conventional cardioplegia. The sample size was determined using a two-tailed hypothesis testing formula with 80% power and 5% significance level. Patient selection employed strict inclusion criteria including age ≥16 years, elective surgery status, LVEF ≥35%, and complete medical records availability. Key preoperative, intraoperative, and postoperative parameters were evaluated, including demographic characteristics, laboratory values, surgical metrics, and clinical outcomes. Preoperative variables included age, gender, weight, body surface area, comorbidities, and baseline laboratory values. Intraoperative measurements focused on aortic cross-clamp time, CPB duration, cardioplegia volume, and hemodynamicparameters. Postoperative outcomes encompassed ICU stay duration, biochemical markers of myocardial injury (Troponin-T, CK-MB), arrhythmias, and mortality rates. The results demonstrated significant differences in postoperative outcomes between the two groups. Patients receiving Del Nido cardioplegia had a markedly shorter ICU stay (5.0 vs. 6.0 days; p < 0.001), lower troponin-T levels (230 vs. 400; p = 0.001), and reduced dopamine consumption (1200 vs. 2400 min; p = 0.001) compared to those receiving conventional cardioplegia. The Del Nido group also showed lower requirements for inotropic support, with reduced durations of both dopamine and noradrenaline administration. Blood drainage volumes were significantly lower in the Del Nido group (median 550.0 mL vs. 890.0 mL; p < 0.001). Notably, no mortality was observed in the Del Nido group, compared to a 2% mortality rate in the conventional group (p = 0.01). The incidence of defibrillation and intra-aortic balloon pump use was also lower in the Del Nido group (p = 0.01 for both variables). However, some parameters showed unexpected variations, such as higher white blood cell counts in the Del Nido group (median 17.20 vs. 12.90; p < 0.001), though this was not clinically significant. Intraoperative parameters, including cross-clamp time and CPB duration, showed no significant differences between the groups, suggesting that Del Nido cardioplegia's benefits manifest primarily in the postoperative period rather than during the procedure itself. The total cardioplegia volume required was lower in the Del Nido group, consistent with its single-dose administration protocol. Safety profiles remained comparable between the two techniques, with no significant differences in major complication rates. Hemoglobin levels, activated clotting time, and transfusion requirements showed similar patterns between groups. Other postoperative markers, including renal and hepatic function parameters, demonstrated no significant variations, supporting the safety of both approaches. This study demonstrates the potential advantages of Del Nido cardioplegia in enhancing postoperative recovery and minimizing complications in adult cardiac surgery. The findings suggest that Del Nido cardioplegia could be considered a viable alternative to conventional approaches, particularly given its efficiency in reducing ICU stay duration and biochemical stress markers. The single-dose administration protocol may contribute to simplified intraoperative management while maintaining equivalent or superior myocardial protection. However, several limitations must be acknowledged, including the retrospective design, relatively small sample size, and single-center nature of the study. These factors may limit the generalizability of findings to broader populations and different clinical settings. Additionally, the focus on short-term outcomes leaves long-term implications unexplored.